The Chain of Things : Divinatory Magic and the Practice of Reading in German Literature and Thought, 1850-1940 - Downing, Eric (Book collections on Project MUSE., 2018)
"Shows how the connection between divinatory magic and reading shaped the experience of reading and aesthetics among nineteenth-century realists and modernist thinkers, including writers, artists, and critics such as Gottfried Keller, Theodor Fontane, and Walter Benjamin"--